Factors impacting school dropout and criminal activities in Urban Belize - Pan-Commonwealth Forum (My University, 2019)
This research provides insight on teacher’s perception of factors affecting completion rates among disadvantage students in two south side schools in urban Belize, Central America. Previous research on causes for increased criminal activity in Belize suggests that school dropout, lack of parental guidance, and unsupportive school environment are major contributing factors. A convenience sample of teachers from two urban low income communities were included in the study. To assess perceptions for increasing levels of dropout among low income students, a Likert scale instrument and open ended items was also utilized. The results from the Mann Whitney test revealed that there is no significant difference p<0.211 for factors pertaining to completion rates among students from disadvantage communities. Teachers perceived that lack of finances, involvement in non-academic activities, lack of parental guidance and support, low levels of motivation and limited academic skills were primary contributing factors. These findings also suggest the need for interventions to cater to students living in poverty stricken and in criminal infested communities. The general view is that unless immediate mentorship and financial support is forthcoming, youths will continue to drop out of secondary schools, crime rates will increase and the many young persons in Belize will lack the opportunity to live productive lives and contribute positively to society.
Pan-Commonwealth Forum, 9-12 September 2019, Edinburgh, Scotland
Keywords: mentorship and support; school dropout; disadvantaged youth